PERANCANGAN IDENTITAS VISUAL BRAND MUSEUM BEKASI: THE BEKASI MUSEUM VISUAL BRAND IDENTITY DESIGN - Nayla Almira Vasthi; Elda Franzia Jasjfi; Agung Eko Budiwaspada (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
The Bekasi Museum Visual Brand Identity Design aims to design a strategy, concept and visual branding identity design for the Bekasi Museum that is in accordance with the image expected by the museum, namely a technology-based history museum. In this design, the method used is the data collection method in the form of observation, interviews, questionnaires and documentation, then the interactive data analysis method (Miles & Hubberman, 1992), and the 5 stage design thinking method consisting of emphatize, define, ideate, prototype, and test. The results of designing the visual identity of the Bekasi Museum brand are the logo, GSM, and its application to the required media.